2022
DOI: 10.3389/fcvm.2022.920399
|View full text |Cite
|
Sign up to set email alerts
|

Hub Genes Identification, Small Molecule Compounds Prediction for Atrial Fibrillation and Diagnostic Model Construction Based on XGBoost Algorithm

Abstract: BackgroundAtrial fibrillation (AF) is the most common sustained cardiac arrhythmia and engenders significant global health care burden. The underlying mechanisms of AF is remained to be revealed and current treatment options for AF have limitations. Besides, a detection system can help identify those at risk of developing AF and will enable personalized management.Materials and MethodsIn this study, we utilized the robust rank aggregation method to integrate six AF microarray datasets from the Gene Expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 79 publications
0
1
0
Order By: Relevance
“…Furthermore, this study identified essential miRNAs such as miR-3123, miR-548g-3p, and miR-9-5p [ 55 ]. Yang et al (2022) pointed out four other hub genes, including CXCL12, LTBP1, LOXL1, and IGFBP3 [ 56 ]. The cytokine CXCL12, which recruits monocytes and lymphocytes, was also indicated by Liu et al (2021) as a hub DEG in AF along with IL7R, TNFSF13B, and CD8A associated with regulatory T cells or natural killer-cell-activated immune cells [ 57 ].…”
Section: Inflammation and Immune Systemmentioning
confidence: 99%
“…Furthermore, this study identified essential miRNAs such as miR-3123, miR-548g-3p, and miR-9-5p [ 55 ]. Yang et al (2022) pointed out four other hub genes, including CXCL12, LTBP1, LOXL1, and IGFBP3 [ 56 ]. The cytokine CXCL12, which recruits monocytes and lymphocytes, was also indicated by Liu et al (2021) as a hub DEG in AF along with IL7R, TNFSF13B, and CD8A associated with regulatory T cells or natural killer-cell-activated immune cells [ 57 ].…”
Section: Inflammation and Immune Systemmentioning
confidence: 99%